How Does an Intensive Exercise Training Changes Irisin and Heat Shock Protein 70 Levels in Trained Males? - Akbulut, Taner (Int Journal Applied Exercise Physiology, 2020)
In this study, it was aimed to investigate the change in irisin and heat shock protein 70 (Hsp70) level of a single intensity exercise which is applied in trained male individuals. Sixty volunteer males who participated in the study regularly training at least three days a week. Blood samples were taken from the participants twice during resting position and after high intensity exercise. Blood samples were separated into serum and plasma by centrifugation. Irisin and Hsp70 levels were determined in serum samples by ELISA method. The data obtained were analyzed using SPSS package program. Paired Samples t test was used to determine the difference between pre-test and post-test values. The significance level was accepted as p <0.01. As a result of the analysis, it was found that there were significant differences statistically between pre and post-exercise values in levels of irisin and Hsp70 (p<0,01). As a result; It has been shown that an heavy exercise increased irisin and Hsp70 levels in trained males. This result is thought to be explained as an increase in the level of irisin as an exercise factor and an increase in the Hsp70 level in parallel with the stress in the organism due to intensive exercise.
Keywords: Training; Single exercise; Intensive; Hormones